Influence of medium chain fatty acids on selected microbes and on in vitro ruminal fermentation of air-exposed corn silage - Salinas-Chavira, Jaime; Arzola-Alvarez, Claudio; Hume, Michael E.; Fonseca, Mozart; Ruiz-Barrera, Oscar; Castillo-Castillo, Yamicela; Ontiveros-Magadan, Marina; Jones, Barbara; Crippen, Tawni L.; Poole, Toni L.; Zuñiga-Serrano, Aracely; Anderson, Robin C. (Frontiers in Veterinary Science, 2024)
Several medium chain fatty acids and different chemical forms of these acids were evaluated in vitro as treatments of aerobically-exposed corn silage against spoilage and pathogenic microbes and for effects on rumen fermentation. Treatments were control (no additive), myristate (MY), laurate (LA), monolaurin (MLA), methyl ester laurate (MELA), a blend of mono-, di- and triglycerides of laurate (BLA), and monocaprylate (MC). After 24 h of aerobic incubation (37°C), yeast and mold growth were not influenced (P > 0.05) by treatments, while the net growth of lactic acid bacteria was decreased, albeit slightly, compared to that by untreated controls (P < 0.01) by all treatments of the air-exposed corn silage. Compared with controls, wild-type enterococci were decreased (P < 0.01) in MLA, MELA, and BLA. Staphylococcus aureus was reduced (P < 0.01) with MLA, MELA, BLA, and MC. Total aerobes showed reductions (P < 0.01) with MLA, BLA, and MC. Listeria monocytogenes numbers were reduced (P < 0.01) with MELA. Anaerobic incubation (24 h; 39°C) of ruminal fluid (10 mL) with 0.2 g air-exposed and MCFA-treated corn silage revealed higher hydrogen accumulations (P < 0.01) with MLA and MC over the control treatment. Methane was decreased (P < 0.01) solely by MLA. There was an increase (P < 0.01) of acetate with MELA and MC; of propionate with MELA or by BLA; and of butyrate with MLA, MELA, BLA, and MC. Total VFA, hexose fermented, and ammonia were increased (P < 0.01) with MELA, BLA, and MC. The acetate:propionate ratio was increased (P < 0.01) with MC. The results showed that treatment of air-exposed corn silage with esterified MCFA had no effect on yeasts and molds but prevented propagation or reduced populations of some unwanted and potentially desirable bacteria. Modest methane reduction was seen during in vitro incubation of rumen fluid suspensions with MLA-treated silage and ammonia accumulations were increased in esterified MCFA-treated silage. Little, if any, other detrimental effects on beneficial ruminal fermentation characteristics were observed.